Chapter 02無料公開

I.1 解答

後生楽 広小路
後生楽 広小路
2021.02.27に更新
z=e^{i\theta}=\cos\theta+i\sin\theta

と変数変換すると

\begin{aligned} \cos\theta&=\frac{z+\bar{z}}{2}\\ &=\frac{1}{2}\left(z+\frac{1}{z}\right)\quad(\because |z|^2=z\bar{z}=1) \end{aligned}

であり

\begin{aligned} \frac{dz}{d\theta}&=ie^{i\theta}\\ &=iz \end{aligned}

である.よって,複素関数G(z)

\begin{aligned} G(z)&=\frac{\cos\theta}{(2+\cos\theta)^2}\frac{1}{\frac{dz}{d\theta}}\\ &=\frac{\frac{1}{2}\left(z+\frac{1}{z}\right)}{\left[2+\frac{1}{2}\left(z+\frac{1}{z}\right)\right]^2}\frac{1}{iz} \end{aligned}
\therefore G(z)=-\frac{2i(z^2+1)}{(z^2+4z+1)^2}\tag{答}

である.